Effect of tilt angle on soiling in perpendicular wind. (December 2019) - Figgis, Benjamin; Goossens, Dirk; Guo, Bing; Ilse, Klemens
Highlights: Soiling of 1-axis PV trackers can be reduced by stowing at maximum tilt toward the wind. Field, wind tunnel, and CFD investigation of soiling of tilted coupons. Most deposition (impacting dust) occurs around 45° tilt toward the wind. Most accumulation (sticking dust) occurs around 22° tilt away from the wind. High fraction of dust particles detach when coupon tilted toward the wind. Abstract: Use of horizontal single-axis trackers in PV power plants is becoming more common, especially with the introduction of bifacial modules. This raises the possibility of combating soiling by adjusting the tracker tilt angle to minimize dust deposition or maximize wind cleaning, at night or when cloudy. In this study we experimentally investigated soiling of coupons tilted about an axis perpendicular to wind, using both an environmental wind tunnel and desert field tests. CFD modeling was also performed to help interpret the experimental results. In the field it was found that maximum deposition (total particles impacting the coupon) occurred when coupons were tilted around 45° toward the wind. However maximum accumulation (particles remaining on the coupon) occurred at 22° tilt away from the wind. The difference was due to a high fraction of particles detaching from coupons when they are tilted toward the wind, which raises flow velocity and shear rate near the surface. The results suggest that to minimize soiling at night, 1-axis PV trackers could be stowed at maximum tilt toward the wind.